The Stillwater Complex: Integrating Zircon Geochronological and Geochemical Constraints on the Age, Emplacement History and Crystallization of a Large, Open-System Layered Intrusion. (28th February 2018) - Wall, Corey J; Scoates, James S; Weis, Dominique; Friedman, Richard M; Amini, Marghaleray; Meurer, William P
Abstract: The Neoarchean Stillwater Complex, one of the world's largest known layered intrusions and host to a rich platinum-group element deposit known as the J-M Reef, represents one of the cornerstones for the study of magmatic processes in the Earth's crust. A complete framework for crystallization of the Stillwater Complex is presented based on the trace element geochemistry of zircon and comprehensive U–Pb zircon–baddeleyite–titanite–rutile geochronology of 22 samples through the magmatic stratigraphy. Trace element concentrations and ratios in zircon are highly variable and support crystallization of zircon from fractionated interstitial melt at near-solidus temperatures in the ultramafic and mafic cumulates (Ti-in-zircon thermometry = 980–720°C). U–Pb geochronological results indicate that the Stillwater Complex crystallized over a ∼3 million-year interval from 2712 Ma (Basal series) to 2709 Ma (Banded series); late-stage granophyres and at least one phase of post-emplacement mafic dikes also crystallized at 2709 Ma. The dates reveal that the intrusion was not constructed in a strictly sequential stratigraphic order from the base (oldest) to the top (youngest) such that the cumulate succession in the complex does not follow the stratigraphic law of superposition. Two distinct age groups are recognized in the Ultramafic series. The lowermost Peridotite zone, up to and including the G chromitite, crystallized at 2710 Ma from magmas emplaced below the overlying uppermost Peridotite and Bronzitite zones that crystallized earlier at 2711 Ma. Based on the age and locally discordant nature of the J-M Reef, the base of this sequence likely represents an intrusion-wide magmatic unconformity that formed during the onset of renewed and voluminous magmatism at 2709 Ma. The thick anorthosite units in the Middle Banded series are older (2710 Ma) than the rest of the Banded series, a feature consistent with a flotation cumulate or 'rockberg' model. The anorthosites are related to crystallization of mafic and ultramafic rocks now preserved in the Ultramafic series and in the lower part of the Lower Banded series below the J-M Reef. The Stillwater Complex was constructed by repeated injections of magma that crystallized to produce a stack of amalgamated sills, some out-of-sequence, consequently it does not constitute the crystallized products of a progressively filled and cooled magma chamber. This calls into question current concepts regarding the intrusive and crystallization histories of major open-system layered intrusions and challenges us to rethink our understanding of the timescales of magma processes and emplacement in these large and petrologically significant and remarkable complexes.